Solve for u 3u^2-2u+4=0

Math
3u2-2u+4=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=3, b=-2, and c=4 into the quadratic formula and solve for u.
2±(-2)2-4⋅(3⋅4)2⋅3
Simplify.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise -2 to the power of 2.
u=2±4-4⋅(3⋅4)2⋅3
Multiply 3 by 4.
u=2±4-4⋅122⋅3
Multiply -4 by 12.
u=2±4-482⋅3
Subtract 48 from 4.
u=2±-442⋅3
Rewrite -44 as -1(44).
u=2±-1⋅442⋅3
Rewrite -1(44) as -1⋅44.
u=2±-1⋅442⋅3
Rewrite -1 as i.
u=2±i⋅442⋅3
Rewrite 44 as 22⋅11.
Tap for more steps…
Factor 4 out of 44.
u=2±i⋅4(11)2⋅3
Rewrite 4 as 22.
u=2±i⋅22⋅112⋅3
u=2±i⋅22⋅112⋅3
Pull terms out from under the radical.
u=2±i⋅(211)2⋅3
Move 2 to the left of i.
u=2±2i112⋅3
u=2±2i112⋅3
Multiply 2 by 3.
u=2±2i116
Simplify 2±2i116.
u=1±i113
u=1±i113
The final answer is the combination of both solutions.
u=1+i113,1-i113
Solve for u 3u^2-2u+4=0

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top